PENERAPAN PENGGUNAAN MEDIA BERBASIS YOUTUBE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI BUDAYA (SENI TARI) SISWA KELAS IV SD NEGERI GRONG-GRONG KABUPATEN PIDIE - Misratul Aula; Aida Fitri; Mislinawati (LPPM Universitas Cipta Mandiri, 2025)
In arts and culture learning (dance), student learning outcomes are still relatively low due to the lack of student involvement in the teaching and learning process. The problem formulation in this study is how student activities and learning outcomes are affected by the application of YouTube as a learning medium in arts and culture learning (dance) on the theme of recognizing the environment through dance. This study investigates the implementation of YouTube-based media in enhancing student engagement and learning outcomes in Dance Art education, specifically the topic